"It helps me find balance": older adult perspectives on the intersection of caregiving and volunteering. Issue 4 (2nd October 2022) - Crittenden, Jennifer A.; Coleman, Rachel L.; Butler, Sandra S.
ABSTRACT: Caregiving is an increasingly prevalent experience that can negatively impact health and well-being. Volunteerism, long associated with positive benefits for older adults, is one potential strategy that can be used to counteract caregiver stress. A national cohort of existing older adult volunteers was engaged to explore the intersection of volunteering and caregiving through qualitative analysis of respondent comments using the lens of role theory. Survey responses from 533 older volunteers were analyzed. Role conflict and role enhancement themes were examined, with time constraints and reduced energy emerging as the perceived causes of conflict between the caregiver and volunteer roles. Caregivers discussed benefits to their caregiving role, including respite, learning, access to information and resources relevant to caregiving, increased socialization and improved physical and cognitive health. Findings indicate that volunteering can be framed as a health and well-being intervention for caregivers.